The Transformation of Monastic Habits: Student Uniforms for Christian Schools in East Asia - Pyun, Kyunghee (Religion and the arts, 2020)
Abstract In this paper, I posit that the transformation of monastic habits is observed and maintained in East Asian school uniforms. School uniforms at the schools founded by religious orders, mainly by Protestant and Catholic missionaries, could have manifested faith and religious identity. These religious authorities, who acted as managers of civic education, coincided with other public and private schools founded in secular contexts, unlike the religious emblems of those groups in their home countries. Many schools founded by Christian missionaries in East Asia in the early twentieth century eliminated a “sacred versus profane” dichotomy in their school uniforms and school symbols. In the formulation of a nation state in East Asia, homogeneity among inhabitants was more important than a faith-based religious identity by each Christian missionary group. Wearers of school uniforms in East Asia were taught to nurture civic identity along with the faith.